As discussões econômicas da constituinte de 1823 e a formação econômica do Primeiro Império - Pereira, Jorge Adriano Schaefer (2009)
The formation of the Brazilian constitutionalism began with the ideas advocated by unconfident miners. This initiative as suppressed by the monarchy. Only later, in 1821, with the independence of Brazil and the world revolt, it started to contemplate the drafting of a constitution of the brazilian Empire to rule the empire and the relationship between the constitutional powers and Brazilian citizens. In 1823 formed the first Constituent Assembly and legislative Council of the Empire of Brazil, with powers to discuss and pass laws and the Charter of Greater nascent empire. In addition to the legislative discussions, appeared the topics relevant economic, political and legal. Inserted into political and economic context in which the nation passed, lawmakers addressed several concerns from themselves, for their salaries, even those related to political and economic elites of Brazil. The country needed to reorganize. The period of the first empire, between 1821 and 1831, was characterized by precipua political and economic instability, in which very diverse interests, clashed constantly. The period was turbulent. The Portuguese and Brazilian elites clashed. The Brazilian economy had its colonial bases, which meant an export economy, slavery, monoculture and primary. Wonder what would be the discussions of economic swayed in the sections of the Parliamentary Assembly in 1823, order to investigate the history of Brazilian constitutionalism and economic discussions in the light microeconomic and macroeconomic, occurring in the parliament of 1823 and, finally, place the period of the First Empire politically and economically